Patterns and impact of longitudinal measurement error for welfare receipt - Johannes Eggs (W. Bertelsmann Verlag (wbv), 2016)
Measurement error is a common phenomenon in the empirical sciences. Longitudinal data can especially be affected by it, as measurement error can influence measures of change, which is one of the primary reasons for collecting longitudinal data in panel surveys. However, measurement error in longitudinal data is rarely analysed. In this series of papers, the measurement error for welfare receipt is analysed for up to five consecutive panel waves by linking panel survey data with administrative data on the individual level. Results from all four studies suggest that measurement error for welfare receipt is highly differential. The measurement error for welfare receipt is not based on a random process, but based on personal characteristics and the welfare histories of the respondents. – – Diese Arbeit beschäftigt sich mit Messfehlern in Längsschnittdaten. Messfehler können in besonderem Maße die Messung von Übergängen und Veränderungen über die Zeit beeinflussen. Die Messung von Veränderungen ist jedoch einer der Hauptgründe für das Erheben von Längsschnittdaten. Allerdings werden Messfehler in Längsschnittdaten selten analysiert. Durch die Verknüpfung von Paneldaten mit Registerdaten auf der individuellen Ebene werden in dieser Arbeit Messfehler für den Bezug von Arbeitslosengeld II für fünf aufeinanderfolgende Panelwellen untersucht. Dabei zeigt sich, dass die Messfehler für den Bezug nicht zufällig verteilt sind, sondern mit der Zeit und persönlichen Charakteristiken korrelieren.
Keywords: 330; Panel; Messung; Statistischer Fehler; Ereignisstudie; Befragung; Sozialleistungsempfänger; Schätzung; Deutschland; Panel; Messung; Statistischer Fehler; Ereignisstudie; Befragung; Theorie; Sozialleistungsempfänger; Schätzung; Deutschland